2020
DOI: 10.3390/ijerph17051665
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Manganese Exposure and Long-Term Neuropsychological Development at 4 Years of Age in a Population-Based Birth Cohort

Abstract: Background: Manganese (Mn) is an essential micronutrient for humans, the diet being the main source of exposure. Some epidemiological studies describe a negative association between prenatal Mn and later neuropsychological development, but results are inconsistent. The aim of this study was to explore the association between prenatal Mn exposure and neuropsychological development assessed at 4 years of age. Methods: Study subjects were 304 mother-child pairs from the Gipuzkoa cohort of the INMA (Environment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Prospective studies found prenatal Mn exposure was not associated with motor outcomes from the McCarthy Scales of Children’s Abilities at 4 or 5 years of age. 47 , 48 Chiu et al. found higher prenatal Mn exposure was associated with better body stability in 11- to 14-y-old adolescent males compared with females.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies found prenatal Mn exposure was not associated with motor outcomes from the McCarthy Scales of Children’s Abilities at 4 or 5 years of age. 47 , 48 Chiu et al. found higher prenatal Mn exposure was associated with better body stability in 11- to 14-y-old adolescent males compared with females.…”
Section: Introductionmentioning
confidence: 99%
“…The results of numerous studies indicate that adverse environmental conditions and stress during fetal development can lead to a whole range of functional and structural disorders in body systems (Scott-Goodwin, Puerto, and Moreno, 2016;Gonzalez-Casanova et al, 2018). Thus, modern experimental and clinical studies have shown the development of pathological changes in the functional parameters of the brain during early postnatal ontogenesis in response to acute exposure to Mn in the prenatal period (Andiarena et al, 2020;Beasley et al, 2022). However, the effects of low-level Mn exposure during prenatal development on adaptive responses, behavior, and cognitive functions of the offspring are still far from being fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The fetus is particularly susceptible to environmental threats. Gestational exposure to environmental toxicants has been related not only to fetal growth and development but also to long-term health challenges [13][14][15]. Thus, assessing the relationship between prenatal pollutants exposure and the features of childhood growth is desirable, and identifying which period of growth is most sensitive to prenatal environmental pollutants exposure is essential for infants' and children's development.…”
Section: Introductionmentioning
confidence: 99%